DI-034 Neurological toxicity caused by ifosfamide in children. (24th February 2014) - Ferrand, AL; Chu, N; Friedl, J; Foucras, G; Viard, C; Perriat, S; Durrieu, G; Vie, M
Abstract : Background: Ifosfamide is used in the treatment of sarcomas, lymphomas and germ-cell tumours. This anti-cancer drug may induce a neurological toxicity known for adults not for children. Purpose: Describing the neurological toxicity of ifosfamide from our experience, in Paediatric Haematology, and the implications on patients. Materials and methods: We performed a retrospective study of reported cases at the regional pharmacovigilance centre for children who presented neurological toxicity due to ifosfamide, from January 2011 to September 2013. Data recorded were: indication, ifosfamide dose, neurotoxicity events, toxicity management and patients' outcomes. Results: We listed five children between one and fifteen years old without any medical history, except one with a tubulopathy. Each child received 3g/m²/course of ifosfamide associated with other anti-cancer drugs. They were treated for nephroblastoma, ewing sarcoma, neuroblastoma and osteosarcoma. They developed neurological toxicity such as convulsions, three generalised convulsions, three encephalopathy, and two comas. Toxicity occurred the second day of the first course except for one child who developed it at the beginning of the sixth. In intensive care unit, they all received methylthioninium chloride to reduce the risk of neurological toxicity. One child got better after a few hours. The others were treated in emergency with diazepam. In addition, three children received clonazepam associated with phenytoin, replaced by phenobarbital for one child, due to its inefficiency. Another must continue antiepileptic treatment. One month after a first encephalopathy and because only ifosfamide can cure metastatic ewing sarcoma, one child received a second course associated to methylthioninium chloride. He had a second encephalopathy and received clonazepam and levetiracetam to be continued after leaving the hospital. Conclusions: Neurological toxicity involved in the use of ifosfamide have been identified and confirmed. Ifosfamide must be used with caution because even associated to methylthioninium chloride the risk of leading to neurological disorders remains. Indeed, two over five children are receiving an antiepileptic treatment today. No conflict of interest.